1996
DOI: 10.1002/(sici)1097-0215(19960621)69:3<225::aid-ijc13>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations in esophageal cancer and their relevance to etiology and pathogenesis: A review

Abstract: o 1996 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
148
2
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(161 citation statements)
references
References 76 publications
10
148
2
1
Order By: Relevance
“…These changes include gene mutations and their frequently associated genomic losses of tumor suppressor genes including p53 (17p13.1 locus) and p16 (9p21 locus). [14][15][16][17][18][19][20] In addition, frequent gains of chromosomes 6, 7, 11, and 12 have been previously reported in adenocarcinomas and adjacent metaplastic epithelium from esophagectomy specimens. 4,21,22 By using endoscopic brushing cytology specimens, we evaluated the ability of FISH to detect molecular genetic changes previously reported to be associated with the malignant transformation in Barrett's esophagus.…”
mentioning
confidence: 99%
“…These changes include gene mutations and their frequently associated genomic losses of tumor suppressor genes including p53 (17p13.1 locus) and p16 (9p21 locus). [14][15][16][17][18][19][20] In addition, frequent gains of chromosomes 6, 7, 11, and 12 have been previously reported in adenocarcinomas and adjacent metaplastic epithelium from esophagectomy specimens. 4,21,22 By using endoscopic brushing cytology specimens, we evaluated the ability of FISH to detect molecular genetic changes previously reported to be associated with the malignant transformation in Barrett's esophagus.…”
mentioning
confidence: 99%
“…The 5-year survival rate is below 10%. 4 In northern China (Lin Xian), where the highest incidence rate of esophageal cancer in the world is found, about 90% of esophageal cancers are SCCs. Epidemiologic studies revealed that, different from adenocarcinomas that developed from Barrett's esophagus, SCCs were more related to dietary habits, tobacco smoking and alcohol drinking.…”
mentioning
confidence: 99%
“…Familial aggregation was also found in SCC, which suggested that genetic alterations play an important role in tumorigenesis of the esophagus. [1][2][3][4] High frequency of LOH has been found on chromosomes 3, 7 and 9. 4 -6 To date, no susceptibility genes for esophageal cancer have been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The development of novel diagnostic or therapeutic strategies requires an in-depth understanding of the molecular mechanisms involved in the complex multistep process of esophageal tumorigenesis. 3 In search of novel molecular targets for esophageal cancer using differential display as described previously, 4 we report for the first time to our knowledge that ␀-mannosidase is overexpressed in esophageal squamous cell carcinoma (ESCC).…”
Section: Dear Sirmentioning
confidence: 98%